Manufacturing method of superabsorbent resin
A multi-stage foaming process with a bubble stabilizer stabilizes bubble formation in high water-absorbing resin, improving water absorption speed and performance by creating a hierarchical structure.
Patent Information
- Application Number
- JP2023579602
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2022-07-18
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2042-07-18
AI Technical Summary
Existing methods for manufacturing high water-absorbing resin face challenges in stabilizing bubbles during the foaming process, leading to unstable bubble formation and difficulty in controlling bubble size, which hinders the creation of a porous structure necessary for high water absorption performance.
A multi-stage foaming process using a bubble stabilizer is employed, involving the preparation of a monomer composition, primary and secondary foaming stages, crosslinking, and subsequent drying and crushing to form a hierarchical bubble structure in the high water-absorbing resin.
The method enables the formation of stable bubbles of varying sizes at each stage, resulting in a resin with enhanced water absorption speed and performance.
Smart Images

Figure 0007625336000002 
Figure 0007625336000003 
Figure 0007625336000004
Abstract
Description
[Technical field]
[0001] Cross-reference to related application(s) This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0093471 filed on July 16, 2021 and Korean Patent Application No. 10-2022-0087601 filed on July 15, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a method for producing a superabsorbent polymer, and more specifically, to a method for producing a superabsorbent polymer with excellent water absorption speed and water absorption performance by forming a hierarchical bubble distribution in the produced superabsorbent polymer through a multi-stage foaming process using a bubble stabilizer. [Background technology]
[0003] Super absorbent polymer (SAP) is a synthetic polymeric material that can absorb 500 to 1,000 times its own weight in water, and each developer has a different name for it, such as SAM (Super Absorbency Material) or AGM (Absorbent Gel Material). These super absorbent polymers first came into practical use as sanitary products, and are now widely used as soil water retaining materials for horticulture, water stoppers for civil engineering and construction, seedling sheets, freshness preserving agents in the food distribution field, and materials for poultices.
[0004] Such superabsorbent polymers are widely used in the field of sanitary materials, such as diapers and sanitary napkins. In the sanitary materials, the superabsorbent polymers are generally contained in a state of being spread in the pulp. However, in recent years, efforts have been made to provide sanitary materials, such as diapers, with thinner thicknesses, and as part of these efforts, the pulp content has been reduced, or even the development of so-called pulpless diapers, which do not use pulp at all, has been actively promoted.
[0005] In sanitary materials such as pulpless diapers, in which the pulp content is thus reduced or no pulp is used, the superabsorbent polymer must not only function as an absorbent that absorbs liquids such as urine, but also as pulp, and therefore must have not only high water absorption performance but also a fast water absorption speed.
[0006] In order to manufacture such a superabsorbent resin having an improved water absorption rate, a method of increasing the specific surface area by introducing a pore structure into the superabsorbent resin is mainly used. Specifically, in order to increase the specific surface area of the superabsorbent resin, a foaming agent may be used in the polymerization step to generate bubbles, or a gas such as carbon dioxide gas, air, or nitrogen gas may be injected.
[0007] However, the bubbles formed by the foaming agent are unstable in the neutralization solution, and therefore the bubbles tend to escape to the outside of the neutralization solution. In particular, it is difficult to control the size of the bubbles, making it impossible to produce a superabsorbent resin having the desired pore structure.
[0008] For this reason, there is a continuing demand for the development of superabsorbent resins that exhibit a high water absorption rate while maintaining the basic water absorption performance of the superabsorbent resins. Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, an object of the present invention is to provide a method for producing a superabsorbent resin which has improved water absorption properties and water absorption speed by forming a hierarchical pore distribution in the produced superabsorbent resin through a multi-stage foaming process using a bubble stabilizer. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention provides preparing a monomer composition including a water-soluble acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, a polymerization initiator, and a first crosslinking agent; a step of subjecting the mixture obtained by mixing the monomer composition with a first foaming agent and a foam stabilizer to a primary foaming process; a step of subjecting the mixture obtained by the first foaming to a second foaming agent; cross-linking and polymerizing the secondary foaming mixture to form a hydrogel polymer; drying, grinding and classifying the hydrogel polymer to form a base resin powder; and The method includes a step of crosslinking at least a portion of the surface of the base resin powder in the presence of a surface crosslinking agent. A method for producing a superabsorbent resin is provided. Effect of the Invention
[0011] According to the method for producing a superabsorbent resin of the present invention, a multi-stage foaming process is carried out using a foaming agent and a foam stabilizer, so that bubbles of different sizes can be easily formed in each stage. As a result, a hierarchical pore structure is formed in the superabsorbent resin that is finally produced through processes such as drying and pulverization, so that the specific surface area can be increased, and the water absorption properties and water absorption speed of the superabsorbent resin can be significantly improved. [Brief description of the drawings]
[0012] [Figure 1] 1 is a schematic diagram showing a multi-stage foaming process in a method for producing a superabsorbent resin according to an embodiment of the present invention. [Diagram 2] 1 is an OM image of bubbles generated under the conditions of the first and second foaming steps in Example 1. [Diagram 3] 1 is a graph showing the change in size of bubbles generated and the size of pores after curing depending on the change in concentration of the bubble stabilizer in the multi-stage foaming process of Example 1. [Figure 4] 1 is a graph showing the particle size distribution of pores in the superabsorbent resins produced in Example 1 and Comparative Example 1. [Diagram 5] 1 is a schematic diagram showing cross-sectional images of superabsorbent resins prepared in Example 1, Comparative Example 1, and Comparative Example 4. [Figure 6]1 shows cross-sectional SEM images of superabsorbent resins prepared in Example 1, Comparative Example 1, and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.
[0014] The term "polymer" or "polymeric polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include all water content ranges or particle size ranges. Among the above polymers, a polymer in a state after polymerization and before drying and having a water content (water content) of about 40% by weight or more can be called a hydrogel polymer, and particles obtained by crushing and drying such a hydrogel polymer can be called a crosslinked polymer.
[0015] In addition, the term "superabsorbent resin particles" refers to a particulate material that includes an acrylic acid monomer having acidic groups, at least a portion of which has been neutralized, and that includes a crosslinked polymer that has been crosslinked by an internal crosslinking agent.
[0016] In addition, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of the acidic groups being neutralized, or a powder-form base resin made of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, depending on the context, or is used to encompass all of the crosslinked polymer or base resin that have been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Thus, the term "super absorbent polymer" can be interpreted as including a plurality of super absorbent polymer particles.
[0017] In addition, the term "bubble" refers to a spherical space formed by foaming gas generated in a mixture during the foaming process, and "pore" refers to a spherical space formed in a hydrogel polymer, base resin, or superabsorbent resin by hardening of the bubble or the like.
[0018] The term "average diameter" of a pore or bubble means the median of the longest diameter of each of the pores or bubbles to be measured, in order to reduce the influence of outliers compared to the simple average.
[0019] The present invention can be modified in various ways and can have various forms, and will be described in detail below by taking specific examples as examples. However, it should be understood that this is not intended to limit the present invention to the specific disclosed forms, but rather to include all modifications, equivalents, or alternatives within the spirit and technical scope of the present invention.
[0020] Furthermore, the terminology used in this specification is for the purpose of referring to particular embodiments only and is not intended to limit the present invention. And, as used herein, the singular forms include the plural forms unless the text clearly indicates otherwise.
[0021] In order to produce a superabsorbent resin having a high water absorption rate, the specific surface area in the superabsorbent resin particles must be increased. Thus, in order to realize a superabsorbent resin with a high specific surface area, a method of forming a large number of pores in the superabsorbent resin by inducing a foaming process during the production process or a method of mechanically deforming the superabsorbent resin has been used. In particular, the size of the foam formed changes depending on how the foaming mechanism is controlled, and this changes the shape of the final particles after pulverization. In order to increase the specific surface area, it is preferable to include a large number of fine pores in the pulverized particles. However, since the bubbles formed in the normal foaming process are unstable in the neutralization solution, the bubbles easily escape outside the neutralization solution, and it is particularly difficult to control the size of the bubbles, making it impossible to produce a superabsorbent resin having the desired pore structure.
[0022] Therefore, the present inventors have confirmed that, when a superabsorbent resin is produced, a multi-stage foaming process using a foaming agent and a foam stabilizer is performed, whereby bubbles of different sizes can be stably formed in each stage, and thus a hierarchical pore structure can be formed in the superabsorbent resin that is finally produced through processes such as drying and pulverization, thereby completing the present invention.
[0023] In particular, it was confirmed that it is easy to control the size of bubbles formed in each foaming stage by adjusting the concentration of the foam stabilizer used together with the foaming agent in the multi-stage foaming process. As a result, the components of the foam stabilizer used in the foaming process and the optimal concentration of the foam stabilizer for each foaming stage were derived to form a more stable pore structure.
[0024] Manufacturing method of superabsorbent resin Hereinafter, each step of a method for producing superabsorbent resin particles according to an embodiment will be described.
[0025] (Preparation of Monomer Composition) First, according to one embodiment of the present invention, the method includes preparing a monomer composition including a water-soluble acrylic acid-based monomer having an acidic group, at least a portion of which is neutralized, a polymerization initiator, and a first crosslinking agent.
[0026] The acrylic acid monomer is a compound represented by the following Chemical Formula 1.
[0027] [Chemical formula 1] R 1 -COOM 1
[0028] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.
[0029] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.
[0030] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline material such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. At this time, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, preferably 40 mol% or more, 60 mol% or more, 70 mol% or more, and 95 mol% or less, 90 mol% or less, 85 mol% or less, or 40 to 90 mol%, 60 to 85 mol%, 70 to 85 mol%. However, if the neutralization degree is too high, the neutralized monomer may precipitate, preventing smooth polymerization, and conversely, if the neutralization degree is too low, the water absorption of the polymer may be significantly reduced, and the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.
[0031] The concentration of the acrylic acid monomer may be 20 to 60% by weight, preferably 20% by weight or more, 40% by weight or more, 60% by weight or less, 50% by weight or less, or 40 to 50% by weight, which may be selected as an appropriate concentration in consideration of polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent resin may be low, which may cause problems in terms of economy, and conversely, if the concentration is too high, problems may occur in the process, such as partial precipitation of the monomer or low pulverization efficiency during pulverization of the polymerized hydrogel polymer, and the physical properties of the superabsorbent resin may be deteriorated.
[0032] In addition, the term "first crosslinking agent" used in this specification is a term used to distinguish it from the second crosslinking agent for mainly crosslinking the surface of the superabsorbent resin particles described later, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is performed regardless of the surface or the inside, but when the surface crosslinking process of the superabsorbent resin particles described later is performed, the particle surface of the finally manufactured superabsorbent resin has a structure crosslinked by the second crosslinking agent, and the inside has a structure crosslinked by the first crosslinking agent.
[0033] As the first crosslinking agent, any compound can be used as long as it can introduce crosslinking bonds during polymerization of the acrylic unsaturated monomer.Specifically, as the first crosslinking agent, a crosslinking agent having one or more functional groups capable of reacting with the water-soluble substituent of the acrylic unsaturated monomer and one or more ethylenically unsaturated groups; or a crosslinking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.
[0034] Non-limiting examples of the first crosslinker include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, Polyfunctional crosslinking agents such as pentaerythritol tri(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerin, or ethylene carbonate can be used alone or in combination of two or more, but are not limited thereto.
[0035] The first crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. For example, the first crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.45 parts by weight or more, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, 0.1 to 3 parts by weight or 0.45 to 1 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the first crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the first crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention ability.
[0036] The monomer composition may further include a polymerization initiator for initiating a polymerization reaction of the monomer. The polymerization initiator is not particularly limited as long as it is generally used in the production of a highly water-absorbent resin.
[0037] Specifically, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator by UV irradiation depending on the polymerization method. However, even if the photopolymerization method is used, a certain amount of heat is generated by irradiation with UV rays, etc., and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may also be included.
[0038] The photopolymerization initiator can be used without any limitation on its constitution as long as it is a compound capable of forming radicals by light such as ultraviolet light.
[0039] The photopolymerization initiator may be at least one selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkylketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, a specific example of the acylphosphine may be commercially available lucirin TPO, i.e., diphenyl(2,4,6-trimethyl benzoyl)phosphine oxide. More various photoinitiators are disclosed in Reinhold Schwalm's book "UV Coatings: Basics, Recent Developments and New Application" (Elsevier, 2007), page 115, and are not limited to the above examples.
[0040] The photopolymerization initiator may be contained in a concentration of about 0.01 to about 1.0% by weight based on the monomer composition. If the concentration of the photopolymerization initiator is too low, the polymerization rate may be slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.
[0041] The thermal polymerization initiator may be at least one selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of the persulfate initiator include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of the azo initiator include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and the like. dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. More various thermal polymerization initiators are disclosed in Principle of Polymerization (Wiley, 1981) by Odian on page 203, and are not limited to the above-mentioned examples.
[0042] The thermal polymerization initiator may be included at a concentration of about 0.001 to about 0.5% by weight based on the monomer composition. If the concentration of the thermal polymerization initiator is too low, additional thermal polymerization hardly occurs, and the effect of adding the thermal polymerization initiator may be insignificant. If the concentration of the thermal polymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.
[0043] The total content of the polymerization initiator can be 2 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. That is, if the concentration of the polymerization initiator is too low, the polymerization rate may be slowed down and a large amount of residual monomer may be extracted in the final product, which is not preferable. On the other hand, if the concentration of the polymerization initiator is higher than the above range, the polymer chain forming the network becomes shorter, the content of water-soluble components increases, and the physical properties of the resin may be deteriorated, such as the water absorption capacity under pressure being reduced, which is not preferable.
[0044] The monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0045] The monomer composition including the monomer may be in a solution state dissolved in a solvent such as water, and the solid content in the monomer composition in such a solution state, i.e., the concentration of the monomer, the first crosslinking agent, and the polymerization initiator, may be appropriately adjusted in consideration of the polymerization time and reaction conditions, etc. For example, the solid content in the monomer mixture may be 10 to 80% by weight, preferably 10% by weight or more, 15% by weight or more, or 30% by weight or more, and may be 80% by weight or less, 60% by weight or less, 50% by weight or less, 15 to 60% by weight, or 30 to 50% by weight.
[0046] When the monomer composition has a solid content within the above range, it is possible to eliminate the need to remove unreacted monomers after polymerization by utilizing the gel effect phenomenon that occurs in the polymerization reaction of a high concentration aqueous solution, and it is also possible to be advantageous in controlling the pulverization efficiency when pulverizing the polymer described below.
[0047] The solvent that can be used at this time may be any solvent capable of dissolving the above-mentioned components, and may be used without limitation in terms of its composition. For example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide may be used in combination.
[0048] Meanwhile, the content of each component in the monomer composition means the total mixed content of the monomer composition in the first foaming step and the monomer composition added in the second foaming step, which will be described later.
[0049] (First foaming stage) Next, the method for preparing a superabsorbent resin according to an embodiment of the present invention includes a step of subjecting the mixture obtained by mixing the monomer composition with a first foaming agent and a cell stabilizer to a primary foaming process.
[0050] In the first foaming step, bubbles are generated by the first foaming agent contained in the mixture of the monomer composition, the first foaming agent, and the foam stabilizer, and the bubbles formed by the foam stabilizer used together can be stably captured in the mixture. The bubbles formed in the first foaming step form a plurality of pores in the hydrogel polymer in the cross-linking polymerization step described below, and form a porous structure in the superabsorbent resin finally manufactured through processes such as drying and pulverization, thereby increasing the specific surface area.
[0051] Meanwhile, the foaming step is carried out at a low temperature of about 50°C or less, as described below, so that bubbles are formed before the polymerization step, and the bubbles stably trapped in the mixture by the bubble stabilizer can form pores in the hydrogel polymer formed in the polymerization step. The first foaming agent can be a low-temperature foaming agent that foams at 50°C or less, so that the foaming process can be carried out before the polymerization step.
[0052] Specific examples of the first foaming agent include one or more selected from the group consisting of sodium carbonate, sodium bicarbonate, potassium bicarbonate, azodicarbonamide, p,p'-oxybisbenzenesulfonylhydrazide, dinitrosopentamethylenetetramine, p-toluenesulfonylhydrazide, and benzenesulfonylhydrazide, and preferably sodium carbonate, potassium bicarbonate, etc.
[0053] In the first foaming step, the first foaming agent may be used in an amount of 200 ppmw to 8,000 ppmw based on the water-soluble ethylenically unsaturated monomer in the mixture, preferably 200 ppmw or more, 500 ppmw or more, 800 ppmw or more, or 8,000 ppmw or less, 6,000 ppmw or less, 4,000 ppmw or less, and may be used in an amount of 500 to 6,000 ppmw or 800 ppmw to 4,000 ppmw. When the first foaming agent is contained within the above content range, the generated fine bubbles can be stably formed. When the content of the first foaming agent is small, the foaming effect is small, and when the first foaming agent is contained in an excessive amount, the gel strength of the finally manufactured superabsorbent resin may be reduced.
[0054] The foam stabilizer is a component that allows the bubbles formed by the foaming agent to be stably trapped within the mixture without escaping outside, and is dispersed at the interface between the mixture and the bubbles formed by the foaming agent to capture and stabilize the bubbles. In addition, the concentration of the foam stabilizer changes between the first foaming stage and the second foaming stage described below, so that the size of the generated bubbles can be controlled.
[0055] Specifically, the higher the concentration of the cell stabilizer in the mixture, the easier it is to stably form fine cells. In the present invention, the cell stabilizer is added in a relatively high concentration in the first foaming stage, and then the foaming agent, monomer, solvent, etc. are added in the second foaming stage to lower the concentration of the cell stabilizer. As a result, fine cells with a relatively small average diameter are formed in the first foaming stage, and cells with a relatively large average diameter are formed in the second foaming stage.
[0056] The foam stabilizer may be a hydrophilic surface-modifying compound, which is located at the interface between the foam formed by the foaming agent and the mixture, allowing the foam to be stably trapped.
[0057] Specifically, the foam stabilizer is a particulate material that is hydrophilically surface-modified and dispersible in the mixture with an average diameter of about 0.05 μm to 5 μm.
[0058] The foam stabilizer is a compound in which a hydrophobic compound has been surface-modified to a hydrophilic state with a specific surface modifier, and specifically, the hydrophobic compound may be surface-modified to a hydrophilic state using one or more polymers or copolymers thereof selected from the group consisting of polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidine, polyvinyl acetate, polyvinylpyrrolidine, polyacrylic acid, polyacrylic amide, polydopamine, poly(4-styrenesulfonate), polyethylene glycol, and polypropylene glycol as a surface modifier.
[0059] The polymer used as the surface modifier can be a homopolymer or a block copolymer.
[0060] The hydrophobic compound may be a compound having a melting point Examples of the hydrophobic synthetic polymer compounds having a melting point of 100° C. or higher include, for example, poly(L-lactide), poly(D,L-lactic acid-co-glycolic acid), polylactic acid, polystyrene, polymethyl methacrylate, polystyrene-polybutadiene copolymer, polystyrene-polyimide copolymer, nylon, and polyester; examples of the hydrophobic natural polymer compounds having a melting point of 100° C. or higher include, for example, lignin, polylactic acid-lignin blends, and cellulose acetate (e.g., cellulose triacetate, cellulose acetate propionate, cellulose acetate butyrate, and cellulose acetate phthalate); examples of the solid hydrocarbon compounds having a melting point of 100° C. or higher include, for example, fatty acids (e.g., stearic acid and palmitic acid), fatty acid metal salts, glyceride esters, and sugar esters; and examples of the hydrophobic compounds used as defoamers and lubricants include particles that can be surface-modified to hydrophilicity (e.g., talc, etc.), but are not limited thereto.
[0061] Meanwhile, when the target of surface modification is an insoluble hydrophobic compound, the hydrophilically surface-modified bubble stabilizer can be surface-modified by dispersing hydrophobic particles and the surface modifier in a mixed solution of water and a cosolvent (acetone, ethanol, etc.) and stirring the mixture. When the target of surface modification is dissolved in an organic solvent, the hydrophobic compound can be surface-modified by dropping the dissolved organic solvent into water to precipitate the organic solvent, or by forming an emulsion and then evaporating the volatile organic solvent.
[0062] The hydrophilic surface-modified bubble stabilizer may be dispersed to have an average diameter of about 0.05 μm to 5 μm when dispersed in a mixture.
[0063] The concentration of the cell stabilizer relative to the total weight of the mixture in the first foaming step is greater than the concentration of the cell stabilizer relative to the total weight of the mixture in the second foaming step, because the second foaming agent is additionally included in the first foaming mixture in the second foaming step, and the relative concentration (content) of the cell stabilizer is reduced.
[0064] Specifically, in the first foaming step, the cell stabilizer may be included in an amount of 0.02 to 1.0 wt% based on the total weight of the mixture, and in this case, the concentration of the cell stabilizer in the second foaming step is smaller than that in the first foaming step. In the first foaming step, the content of the cell stabilizer is preferably 0.02 to 0.05 wt%, 0.1 to 0.3 wt%, 1.0 to 0.8 wt%, or 0.5 to 0.5 wt%, and may be included in an amount of 0.05 to 0.8 wt% or 0.3 to 0.5 wt%. When included within the above content range, the generated cells can be stably formed, and in particular, the diameter of the generated cells can be controlled to 100 nm or less. Therefore, in the first foaming step, fine cells having a diameter of 100 nm or less can be formed.
[0065] The primary blowing agent and the cell stabilizer may be used as a primary blowing agent composition in which they are dissolved or dispersed.
[0066] The first foaming agent composition may further include an additional solvent for dissolving or dispersing the first foaming agent and the foam stabilizer. Examples of the solvent include water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, and mixtures thereof, and preferably water.
[0067] The primary foaming step may be performed at 35°C to 50°C, preferably 35°C or more, 40°C or more, and 50°C or less, in which the first foaming agent foams and fine bubbles can be easily trapped in the mixture.
[0068] In the primary foaming step, fine bubbles having a diameter of 100 nm or less are formed. The diameter of the fine bubbles may be preferably 20 nm or more, 100 nm or less, or 20 to 100 nm. The fine bubbles are stably captured in the mixture by the high concentration of bubble stabilizer, and contribute to the formation of fine pores having a diameter of 2 μm to 180 μm in the superabsorbent resin finally produced through an additional foaming process, a cross-linking polymerization process, a surface cross-linking process, a pulverization process, etc.
[0069] (Secondary foaming stage) Next, the method for producing a superabsorbent resin according to an embodiment of the present invention includes a step of subjecting the mixture obtained by mixing the first foaming mixture with a second foaming agent to a second foaming process.
[0070] Here, the primary foaming mixture means a mixture that is primarily foamed and contains fine bubbles.
[0071] After the first foaming, additional bubbles are generated through the second foaming stage, which is generated by the foaming agents (the remaining first foaming agent and the added second foaming agent) in the mixture. The bubbles generated in the second foaming stage can be stably trapped in the mixture by the foam stabilizer present in the first foaming mixture.
[0072] However, since no additional bubble stabilizer is added in the secondary foaming stage, the concentration of the bubble stabilizer in the mixture is relatively low in the secondary foaming stage. As a result, the bubbles formed in the secondary foaming stage have a larger average diameter than the bubbles formed in the primary foaming stage. In addition, the particle size of the bubbles formed in the primary foaming stage and the bubbles formed in the secondary foaming stage allows a hierarchical porous structure to be realized in the final superabsorbent resin.
[0073] The second foaming agent may be the same as the first foaming agent.
[0074] The content of the second blowing agent is the same as that of the first blowing agent, and may be added depending on the monomer content when a monomer is added in the second foaming step as described below. Specifically, the content of the second blowing agent may be 200 ppmw to 8,000 ppmw based on the water-soluble ethylenically unsaturated monomer in the mixture to be foamed, and preferably 200 ppmw or more, 500 ppmw or more, 800 ppmw or more, or 8,000 ppmw or less, 6,000 ppmw or less, 4,000 ppmw or less, and may be 500 to 6,000 ppmw or 800 ppmw to 4,000 ppmw. When the content is within the above range, the bubbles generated may be stably formed.
[0075] The second blowing agent can be used as a second blowing agent composition containing an additional solvent, which can be the same solvent as that used in the first blowing agent composition.
[0076] Meanwhile, in the second foaming stage, the concentration of the foam stabilizer contained in the mixture becomes smaller than that in the first foaming stage, and the concentration becomes 0.1 to 0.5 times lower than that in the first foaming stage (this means that the mixture to be foamed is diluted 2 to 10 times).
[0077] Specifically, the concentration of the cell stabilizer may be relatively reduced depending on the content of the second foaming agent composition added, and the concentration of the cell stabilizer may be reduced by adding an additional monomer composition in the second foaming step.
[0078] The monomer composition additionally added in the second foaming step may include a water-soluble acrylic acid-based monomer having an acid group and at least a portion of the acid group being neutralized, a polymerization initiator, and a first crosslinking agent. The components and contents of the water-soluble acrylic acid-based monomer, the polymerization initiator, and the first crosslinking agent are as described above.
[0079] The secondary foaming step may be carried out at 35° C. to 50° C., in which the foaming agent foams and air bubbles can be easily trapped in the mixture.
[0080] In the second foaming step, bubbles having a particle size 2 to 10 times larger than that of the bubbles formed in the first foaming process may be formed.
[0081] Specifically, when fine bubbles having a diameter of 100 nm or less are formed in the first foaming step, bubbles having a diameter of 100 nm to 1,000 nm may be formed in the second foaming step. Preferably, the diameter of the bubbles is 100 nm or more, 150 nm or more, 1,000 nm or less, 500 nm or less, 400 nm or less, or 250 nm or less, and may be 100 nm to 500 nm, 100 nm to 400 nm, or 150 nm to 250 nm. The bubbles contribute to the formation of pores having an average diameter of 180 μm or more in the superabsorbent resin finally produced through a cross-linking polymerization process, a surface cross-linking process, a pulverization process, etc.
[0082] Meanwhile, if necessary, the above-mentioned foaming step can be additionally performed several times, and the concentration of the foam stabilizer can be adjusted in the additional foaming step to form foams with different average diameter sizes.
[0083] (Cross-linking polymerization stage) Next, the method for producing a superabsorbent resin according to an embodiment of the present invention includes a step of cross-linking and polymerizing the secondary foaming mixture to form a hydrous gel polymer.
[0084] Here, the secondary foaming mixture contains hierarchical bubbles formed in the primary and secondary foaming steps. The bubbles contained in the secondary foaming mixture are stably trapped in the foaming mixture by the bubble stabilizer, and the bubbles form pores in the hydrogel polymer formed in the cross-linking polymerization step. Specifically, a hierarchical porous pore structure having different average diameters is formed in the hydrogel polymer.
[0085] The cross-linking polymerization step can be carried out at 50° C. to 100° C., which is a higher temperature than the temperature of the foaming step. When polymerization is carried out within this temperature range, bubbles formed in the foaming step can form an appropriate pore structure in the hydrogel polymer.
[0086] The crosslinking polymerization method is largely classified into thermal polymerization and photopolymerization depending on the polymerization energy source. In general, thermal polymerization can be carried out in a reactor having a stirring shaft such as a kneader, and photopolymerization can be carried out in a reactor equipped with a movable conveyor belt. However, the above-mentioned polymerization methods are merely examples, and the present invention is not limited to the above-mentioned polymerization methods.
[0087] For example, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft or heating the reactor as described above may have a shape of several centimeters to several millimeters when discharged from the reactor outlet depending on the shape of the agitator shaft equipped in the reactor. Specifically, the size of the obtained hydrogel polymer may vary depending on the concentration of the monomer composition injected and the injection speed, but a hydrogel polymer having a weight average diameter of 2 to 50 mm is usually obtained.
[0088] In addition, when photopolymerization is performed in a reactor equipped with a movable conveyor belt as described above, the form of the obtained hydrogel polymer may be a sheet-like hydrogel polymer having the width of the belt. At this time, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition injected, but it is preferable to supply the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 5 cm is obtained. If the monomer composition is supplied so that the thickness of the sheet-like polymer is too thin, it is not preferable because the production efficiency is low, and if the thickness of the sheet-like polymer exceeds 5 cm, the polymerization reaction may not occur uniformly throughout the entire thickness due to the excessively thick thickness.
[0089] The water content of the hydrogel polymer obtained by this method may be about 40 to about 80% by weight. Meanwhile, throughout this specification, the "water content" refers to the water content relative to the total polymer weight, and means the weight of the polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to the evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer through infrared heating. Here, the drying conditions are a method of increasing the temperature from room temperature to about 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase stage, and the water content is measured.
[0090] (Drying, grinding and classification stages) Next, according to one embodiment of the invention, the method includes drying, pulverizing and classifying the hydrogel polymer to form a base resin powder.
[0091] Specifically, the obtained hydrogel polymer is dried, and if necessary, the hydrogel polymer may be coarsely pulverized before drying in order to increase the efficiency of the drying step.
[0092] In this case, the crusher used is not limited in structure, and specifically may include any one selected from the group of crushing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.
[0093] In this case, the coarse pulverization step can pulverize the hydrogel polymer to a particle size of 2 to 10 mm. It is technically difficult to pulverize the hydrogel polymer to a particle size of less than 2 mm due to the high water content of the hydrogel polymer, and the pulverized particles may aggregate with each other. On the other hand, if the particle size is pulverized to a particle size of more than 10 mm, the efficiency increase effect of the subsequent drying step may be insignificant.
[0094] The hydrogel polymer that has been coarsely pulverized as described above or that has not been subjected to the coarse pulverization step is dried immediately after polymerization. In this case, the drying step is performed at a temperature of 150° C. or more for 30 minutes or more. The drying temperature may be 150° C. to 250° C. or 170° C. to 200° C. If the drying temperature is less than 150° C., the drying time may be too long, and the physical properties of the superabsorbent polymer that is finally formed may be deteriorated. If the drying temperature is more than 250° C., only the polymer surface may be dried excessively, and fine powder may be generated in the subsequent pulverization step, and the physical properties of the superabsorbent polymer that is finally formed may be deteriorated.
[0095] On the other hand, the drying step is carried out for 30 minutes or more. If it is carried out for less than 30 minutes, the drying is not sufficient. It is preferably carried out for 30 to 90 minutes, but is not limited thereto.
[0096] The drying method of the drying step can be selected and used without any limitation on the structure as long as it is a method commonly used for drying hydrogel polymers. Specifically, the drying step can be performed by hot air supply, infrared radiation, ultrashort wave radiation, ultraviolet radiation, etc. The water content of the polymer after the drying step can be about 0.1 to about 10% by weight.
[0097] Next, the dried polymer obtained through the drying step is pulverized.
[0098] The polymer powder obtained after the pulverization step may have a particle size of 300 μm to 800 μm. The pulverizer used for pulverizing to such a particle size may be, but is not limited to, a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill.
[0099] After the pulverization step, in order to control the physical properties of the superabsorbent resin powder to be manufactured as a final product, a separate process of classifying the polymer powder obtained after pulverization according to particle size can be performed. Preferably, the polymer having a particle size of 300 μm to 800 μm is classified, and only the polymer powder having such a particle size can be manufactured as a product through the surface crosslinking reaction step. More specifically, the base resin powder that has been classified has a particle size of 300 μm to 800 μm, and may contain 50% by weight or more of particles having a particle size of 300 to 600 μm.
[0100] (Surface crosslinking process) Meanwhile, according to one embodiment of the present invention, after the base resin powder is prepared through the above-mentioned classification process, a step of crosslinking at least a part of the surface of the base resin powder in the presence of a surface crosslinking agent is included.
[0101] The base resin powder is heat-treated in the presence of a second crosslinking agent to thermally crosslink at least a portion of the surface of the base resin powder to form superabsorbent resin particles. The surface crosslinking step induces a crosslinking reaction on the surface of the base resin powder in the presence of a second crosslinking agent, and a surface crosslinked layer can be formed on at least a portion of the surface of the base resin powder through the surface crosslinking. This is to increase the surface crosslinking density of the superabsorbent resin, and when the superabsorbent resin further includes a surface crosslinked layer as described above, the superabsorbent resin has a structure in which the crosslinking density is higher on the outside than on the inside.
[0102] The surface cross-linking step may be carried out at a temperature of about 180° C. or greater for about 30 minutes or greater.
[0103] The second crosslinking agent may be any of the second crosslinking agents used in the manufacture of existing superabsorbent resins without any particular limitations. For example, the second crosslinking agent may include at least one polyol selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol; at least one carbonate-based compound selected from the group consisting of ethylene carbonate and propylene carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; mono-, di-, or polyoxazolidinone compounds; or cyclic urea compounds. Preferably, the same as the first crosslinking agent described above can be used, for example, a diglycidyl ether compound of an alkylene glycol such as ethylene glycol diglycidyl ether can be used.
[0104] The second crosslinking agent can be used in an amount of 0.001 to 2 parts by weight based on 100 parts by weight of the base resin powder. Preferably, the amount is 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.02 parts by weight or more, and 0.5 parts by weight or less, or 0.3 parts by weight or less. By adjusting the content range of the second crosslinking agent within the above range, a superabsorbent resin exhibiting various physical properties such as excellent water absorption performance and liquid permeability can be produced.
[0105] Meanwhile, the superabsorbent resin according to an embodiment may further use aluminum salts such as aluminum sulfate salts and other various polyvalent metal salts during surface cross-linking in order to further improve liquid permeability, etc. Such polyvalent metal salts may be included on the surface cross-linked layer of the final superabsorbent resin.
[0106] Meanwhile, the superabsorbent resin according to one embodiment of the present invention may have a particle size of 300 to 800 μm. More specifically, at least 95% by weight of the base resin powder and the superabsorbent resin containing the same may have a particle size of 300 to 800 μm, and may contain 50% by weight or more of particles having a particle size of 300 to 600 μm.
[0107] (Super absorbent resin) The superabsorbent resin produced by the method for producing a superabsorbent resin according to an embodiment of the present invention includes a plurality of pores, and the average diameter of the plurality of pores may be 20 μm to 150 μm through the multi-stage foaming process of the present invention described above.
[0108] Furthermore, 70% or more of the pores are micropores having a diameter of 2 μm to 180 μm, so that the superabsorbent resin has a hierarchical pore structure. The ratio of the micropores is preferably 70% or more, 73% or more, 78% or more, 81% or more, or 84% or more, and 99% or less, 95% or less, or 92% or less, or 70 to 99%, or 73 to 92%.
[0109] Normally, even if a foaming process is performed, the formed fine bubbles easily disappear through processes such as polymerization and pulverization. However, as described above, in the present invention, by performing a multi-stage foaming process using a bubble stabilizer, a large number of fine pores having a diameter of 2 μm to 180 μm exist in the final superabsorbent resin, and the water absorption speed can be significantly improved.
[0110] On the other hand, if a multi-stage foaming process is not performed during the preparation of the superabsorbent resin, or if a multi-stage process is performed but the cell stabilizer of the present invention is not used, it is difficult to introduce the hierarchical pore structure aimed at by the present invention.
[0111] Here, the average diameter of the pores in the superabsorbent resin can be confirmed by observing the internal structure of the superabsorbent resin particles to be measured using an optical microscope (OM; magnification: X50 or X500) and an electron microscope (SEM; magnification: X200 or X5000). More specifically, the longest diameter of each pore contained in the superabsorbent resin particle can be measured, and the median of the measured longest diameters can be determined as the average diameter. Here, it is preferable to measure the diameters of 800 or more pores for one superabsorbent resin sample and then determine the average diameter.
[0112] The content of micropores having a diameter of 2 μm to 180 μm means the ratio of the number of micropores having a diameter of 2 μm to 180 μm among the longest diameters of 800 or more pores in one superabsorbent resin sample.
[0113] Meanwhile, the superabsorbent resin may contain particles having a particle size of about 300 μm to about 800 μm in an amount of 90% by weight or more based on the total weight, and the particle size of the superabsorbent resin particles may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.
[0114] The superabsorbent resin may have a centrifugation retention capacity (CRC) of 28 g / g or more, preferably 28.8 g / g or more, 29.5 g / g or more, and 35 g / g or less, 33 g / g or less, 31.7 g / g or less, 28 to 35 g / g, or 28.8 to 31.7 g / g, as measured by the EDANA method WSP 241.3. The method for measuring the centrifugation retention capacity (CRC) will be described in more detail in the Experimental Examples section below.
[0115] The superabsorbent polymer has a water absorption speed (vortex time) of 40 seconds or less by a vortex method. The smaller the water absorption speed, the better. The lower limit of the water absorption speed is theoretically 0 seconds, but may be, for example, 5 seconds or more, 10 seconds or more, 20 seconds or more, 40 seconds or less, 38 seconds or less, 37 seconds or less, 35 seconds or less, 33 seconds or less, 32 seconds or less, 31 seconds or less, or 10 seconds to 40 seconds. The water absorption speed by the vortex method means the time (unit: seconds) at which the vortex of the liquid disappears due to fast water absorption when the superabsorbent polymer is added to physiological saline and stirred, and the shorter the time, the faster the superabsorbent polymer has an initial water absorption speed. Here, physiological saline means a 0.9 wt % sodium chloride (NaCl) aqueous solution. The method for measuring the water absorption speed will be described in more detail in the experimental examples described later. On the other hand, the water absorption rate by the vortex method can be measured by the same method for the base resin powder before surface crosslinking.
[0116] The present invention will be described in more detail with reference to the following examples, however, the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.
[0117] <Production Example> The first foaming agent composition containing a foam stabilizer used in the following examples was prepared as follows.
[0118] Production Example 1-1: Production of first foaming agent composition (A-1) First, 500 g of water containing a PEO copolymer (Pluronic® F-127, Sigma-Aldrich) at a concentration of 0.25% w / v was placed in a high shear mixer, and while stirring at 20,000 rpm at room temperature (24±1°C) and normal pressure (1 atm), dichloromethane containing 15% w / v polylactic acid (Poly(L-lactide), average Mn 20,000, Sigma-Aldrich) was added at 20% v / v. After the addition of dichloromethane, the mixture was stirred at 20,000 rpm for an additional 15 minutes to form an oil-in-water emulsion.
[0119] After that, dichloromethan was evaporated while stirring slowly for 20 hours to form a PLA bubble stabilizer surface-modified with PEO copolymer. The bubble stabilizer was collected by centrifugation and redispersed in water, and the average diameter of the bubble stabilizer in the aqueous dispersion was 0.3 μm.
[0120] 9 g of the foam stabilizer prepared above was added to 800 g of water (here, the total water content was adjusted to 800 g, taking into consideration the water content in the aqueous dispersion containing the foam stabilizer). Next, 1.35 g of sodium bicarbonate (SBC) was added as the first foaming agent and stirred at room temperature (24±1° C.) to prepare a first foaming agent composition.
[0121] Production Example 1-2: Production of first foaming agent composition (A-2) In Preparation Example 1-1, when preparing the aqueous dispersion of the bubble stabilizer, PLA / lignin (added to an organic solvent at a weight ratio of 9:1) was used in place of PLA at the same content, and the average diameter of the bubble stabilizer in the aqueous dispersion was 0.3 μm.
[0122] Except for the above, a first foaming agent composition (A-2) was produced in the same manner as in Production Example 1-1.
[0123] Production Example 1-3: Production of first foaming agent composition (A-3) In Preparation Example 1-1, PE / PP wax (LG Chem) was used in place of PLA at the same content, and the average diameter of the bubble stabilizer in the aqueous dispersion was 0.2 μm.
[0124] Except for the above, a first foaming agent composition (A-3) was produced in the same manner as in Production Example 1-1.
[0125] Production Example 1-4: Production of first foaming agent composition (A-4) In Preparation Example 1-1, cellulose ester (180955, Sigma-Aldrich) was used in place of PLA at the same content, and the average diameter of the bubble stabilizer in the aqueous dispersion was 0.6 μm.
[0126] Except for the above, a first foaming agent composition (A-4) was produced in the same manner as in Production Example 1-1.
[0127] Production Example 1-5: Production of first foaming agent composition (A-5) In Preparation Example 1-1, magnesium stearate (415057, Sigma-Aldrich) was used in the same amount instead of PLA, and the average diameter of the bubble stabilizer in the aqueous dispersion was 2 μm.
[0128] Except for the above, a first foaming agent composition (A-5) was produced in the same manner as in Production Example 1-1.
[0129] Production Example 1-6: Production of first foaming agent composition (A-6) In Preparation Example 1-1, polyvinyl alcohol (360627, Mw 9,000-10,000, Sigma-Aldrich) was used in the same amount instead of the surface modifier PEO copolymer, and the average diameter of the bubble stabilizer in the aqueous dispersion was 0.3 μm.
[0130] Except for the above, a first foaming agent composition (A-6) was produced in the same manner as in Production Example 1-1.
[0131] Production Example 1-7: Production of first foaming agent composition (A-7) A first foaming agent composition (A-7) was prepared in the same manner as in Preparation Example 1-1, except that potassium bicarbonate (DUKSAN) was used in the same amount instead of the foaming agent SBC in Preparation Example 1-1.
[0132] <Examples and Comparative Examples> Example 1 (Step 1) 5,000g of acrylic acid, 1,750g of NaOH, and 2,300g of water were slowly added dropwise to a glass container equipped with a stirrer and a thermometer to prepare a mixture. A solution containing 615g of water, 4.5g of IRGACURE 819 as a photoinitiator, 9g of sodium persulfate as a thermal initiator, and 22.5g of polyethylene glycol diacrylate (PEGDA, molecular weight 400g / mol) as a first crosslinking agent was slowly added dropwise to prepare a monomer composition. The neutralization degree of acrylic acid in the obtained composition was 70 mol%.
[0133] (Step 2) The prepared monomer composition was put into a transfer pipe, and the first foaming agent composition of Preparation Example 1 was added. Here, the content of the first foaming agent SBC was added so as to be 1,500 ppmw of acrylic acid (the foam stabilizer of Preparation Example 1 was added at a content increased by 5.5 times), and at this time, the foam stabilizer was included at 0.36 wt% based on the total weight of the mixture.
[0134] The mixture was heated to 50° C. to carry out the first foaming. The flow rate was adjusted so that the Reynolds number was 5,000 or more so that the monomer composition and the first foaming agent composition could be easily mixed inside the transfer pipe.
[0135] (Step 3) The monomer composition prepared above was added to the first foaming mixture, and the second foaming agent composition in which SBC was dispersed in water was added in order to make the SBC content 1,500 ppmw relative to the total monomer content in the mixture. The second foaming mixture was heated to 50° C. to carry out the second foaming.
[0136] At this time, the content of the additional monomer composition was adjusted so that the concentration of the cell stabilizer was 0.036 wt% relative to the total content of the mixture (adjusted so that the cell stabilizer was diluted 10 times). However, after the first foaming process, some of the cell stabilizer was absorbed at the interface and consumed, so the concentration of the cell stabilizer in the mixture was slightly reduced.
[0137] The flow rate was adjusted so that the Reynolds number was 5,000 or more so that each component could be easily mixed inside the transfer tube.
[0138] Meanwhile, a flow chart of the multi-stage foaming process according to Example 1 is shown in FIG.
[0139] (Step 4) The secondary foaming mixture coming out of the transfer pipe was fed at a speed of 500 to 2000 mL / min onto a conveyor belt 10 cm wide and 2 m long rotating at a speed of 50 cm / min. Simultaneously with the feeding of the secondary foaming mixture, a 10 mW / cm 2 The polymerization reaction was carried out for 60 seconds by irradiating ultraviolet light having an intensity of 100 nm to obtain a sheet-shaped hydrogel polymer having a water content of 55% by weight.
[0140] (Step 5) Next, the sheet-shaped hydrogel polymer was cut into pieces of about 5 cm x 5 cm, and then put into a meat chopper to crush the polymer, obtaining hydrogel particle powder (crumb) having a size of 1 mm to 10 mm. The powder (crumb) was then dried in an oven capable of shifting the air flow up and down. Hot air of 180°C or higher was blown from bottom to top for 15 minutes, and then from top to bottom for another 15 minutes to dry uniformly, so that the moisture content of the dried body after drying was 2% or less. After drying, the powder was crushed in a crusher and classified to select a size of 300 to 800 μm to prepare a base resin powder.
[0141] (Step 6) 6 parts by weight of a second crosslinking agent aqueous solution containing 3 parts by weight of ethylene carbonate was sprayed onto 100 parts by weight of the prepared base resin powder, and the mixture was stirred at room temperature to uniformly distribute the surface crosslinking liquid on the base resin powder. Then, the base resin powder mixed with the surface crosslinking liquid was placed in a surface crosslinking reactor to carry out a surface crosslinking reaction.
[0142] In the surface crosslinking reactor, the base resin powder was gradually heated from an initial temperature of about 80°C, and was operated so as to reach a maximum reaction temperature of 190°C after 30 minutes. After reaching the maximum reaction temperature, the reaction was continued for an additional 15 minutes, and then a final superabsorbent resin sample was taken. After the surface crosslinking process, the superabsorbent resin of Example 1 having a particle size of 300μm to 800μm was produced by classifying the particles using a standard mesh sieve according to the ASTM standard.
[0143] Examples 2 to 7 Superabsorbent resins were produced in the same manner as in Example 1, except that the first foaming agent compositions (A-2 to A-7) produced in Production Examples 2 to 7 were used.
[0144] Comparative Example 1 The same foam stabilizer and foaming agent as in Example 1 were used, but the foaming process was not performed in the first high concentration (foam stabilizer: 0.36 wt%) foaming step, and was performed under the same conditions as in the second low concentration (foam stabilizer: 0.036 wt%) foaming step. A superabsorbent resin was produced in the same manner as in Example 1.
[0145] Comparative Example 2 A superabsorbent resin was produced in the same manner as in Example 4, except that the same bubble stabilizer and foaming agent were used as in Example 4, but the first high concentration (bubble stabilizer: 0.36 wt%) foaming process was not performed, and the second low concentration (bubble stabilizer: 0.036 wt%) foaming process was performed under the same conditions.
[0146] Comparative Example 3 In Example 1, when preparing the first foaming agent composition of Preparation Example 1, polystyrene (LG Chem, latex beads 0.3 μm) was used as a foam stabilizer at the same content, but the first high concentration (foam stabilizer: 0.36 wt%) foaming process was not performed, and the second low concentration (foam stabilizer: 0.036 wt%) foaming process was performed under the same conditions. A superabsorbent resin was prepared in the same manner as in Example 1.
[0147] Comparative Example 4 A highly water-absorbent resin was produced in the same manner as in Example 1, except that no cell stabilizer was used.
[0148] Comparative Example 5 A solution (solution A) was prepared by mixing 8.6 g of IRGACURE 819 initiator (80 ppmw relative to monomer) diluted to 0.5 wt% in acrylic acid and 12.3 g of polyethylene glycol diacrylate (PEGDA, Mw = 400) diluted to 20 wt% in acrylic acid. 540 g of acrylic acid and the solution A were poured into a 2 L glass reactor surrounded by a jacket in which a heat medium circulated and pre-cooled to 25 ° C. Then, 832 g of 25 wt% caustic soda solution (solution C) was gradually added dropwise to the glass reactor and mixed. After confirming that the temperature of the mixed solution rose to about 72 ° C. or more due to the heat of neutralization, the mixed solution was allowed to cool. The neutralization degree of acrylic acid in the mixed solution thus obtained was about 70 mol %. Separately, water was put into a microbubble device (O2 bubble, OB-750S) that circulates at a flow rate of 500 kg / h per hour to generate bubbles to produce solution D. Silica was added to this solution and placed in an ultrasonic device (O2 bubble, OB-750S) to produce solution F. When the temperature of the neutralized mixed solution was cooled to about 45°C, previously prepared solution F was added and mixed into the mixed solution. At this time, the amount of silica was 0.05 parts by weight per 100 parts by weight of the mixed solution.
[0149] Next, the mixed solution prepared above was poured into a vat-shaped tray (15cm x 15cm) installed in a square polymerization vessel with a light irradiation device attached on top and the inside preheated to 80°C. Then, the mixed solution was irradiated with light. It was confirmed that a gel was formed on the surface about 20 seconds after the light irradiation, and that a polymerization reaction occurred simultaneously with foaming about 30 seconds after the light irradiation. Next, the polymerization reaction was carried out for an additional 2 minutes, and the polymerized sheet was taken out and cut into pieces of 3cm x 3cm. Then, the cut sheet was chopped using a meat chopper to produce a powder. The average particle size of the produced powder was 1.5mm. Next, the powder was dried in an oven with an adjustable air volume up and down. In order to make the moisture content of the dried powder about 2% by weight or less, hot air at 180°C was blown from bottom to top for 15 minutes, and then blown from top to bottom for another 15 minutes to dry the crump evenly. The dried powder was crushed in a crusher and classified to obtain a base resin with a size of 150 to 850 μm.
[0150] Then, 100 g of the prepared base resin was mixed with a crosslinking agent solution of 4.5 g of water, 1 g of ethylene carbonate, 0.05 g of Aerosil 200 (Evonik), and 0.25 g of 20 wt% water-dispersed silica (Snowtex, ST-O) solution, and the surface crosslinking reaction was carried out at 190°C for 30 minutes. The obtained product was then crushed and sieved to obtain a surface crosslinked superabsorbent resin with a particle size of 150 to 850 μm. 0.1 g of Aerosil 200 was added to the obtained superabsorbent resin in a dry mixing manner to produce a superabsorbent resin.
[0151] <Experimental Example> Experimental example 1: Measurement of bubble size in a multi-stage foaming process (1-1) In order to confirm the structure of bubbles generated in the multi-stage foaming process among the manufacturing processes of Example 1, the foaming mixture at each foaming stage was photographed at a magnification of 50 to 500 using an optical microscope (product name: Ti-U, manufacturer: Nikon). Specifically, the OM images of bubbles in the primary foaming mixture and the secondary foaming mixture are shown in FIG. 2 by the following method.
[0152] Figure 2(a) shows bubbles generated after the first foaming process (foaming under high concentration of foam stabilizer), and Figure 2(b) shows bubbles generated after the second foaming process (foaming under low concentration of foam stabilizer). Referring to Figure 2(a), it can be seen that the first foaming process contains a relatively high concentration of foam stabilizer and fine bubbles with small diameters are trapped in the foaming mixture, and referring to Figure 2(b), it can be seen that the second foaming process contains a relatively low concentration of foam stabilizer compared to the first foaming process and bubbles with relatively large diameters are trapped in the foaming mixture.
[0153] (1-2) In the manufacturing process of Example 1, the concentration of the bubble stabilizer was varied in the multi-stage foaming process, and the size of the bubbles generated during the foaming process was measured using the OM image of Experimental Example 1 (1-1), and the size of the pores after curing was measured using the SEM image of Experimental Example 2 described below. The changes are shown in the graph of FIG. 3.
[0154] Referring to FIG. 3, it can be seen that the higher the concentration of the bubble stabilizer in the foaming process, the smaller the size of the generated bubbles becomes.
[0155] Experimental Example 2: Measurement of pore size of superabsorbent resin To confirm the pore structure of the superabsorbent resins prepared in the Examples and Comparative Examples, internal images of superabsorbent resin particles were taken at 200 to 5,000 magnifications using a SEM (Scanning Electron Microscope, product name: JCM-6000, manufacturer: JEOL). Specifically, the average diameter of the pores of the superabsorbent resin was measured by the following method. As a result, the pore size distributions for Example 1 and Comparative Example 1 are shown in FIG. 4. In addition, cross-sectional images for Example 1, Comparative Example 1, and Comparative Example 4 are shown in FIG. 5 and FIG. 6, respectively.
[0156] 1) First, the examples and the superabsorbent resin were classified for 1 minute at 1.0 amplitude using a particle classifier manufactured by Retsch Corporation to prepare 2 g of a sample separated into individual particles having particle sizes of 200 μm to 500 μm without damaging the particles.
[0157] 2) Then, the prepared sample particles were randomly arranged and placed on the SEM stage.
[0158] 3) Next, the sample particles randomly arranged on the SEM stage were fixed with carbon tape, and the size of the pores formed on the surface of the superabsorbent particles was measured at a magnification of 200 to 5,000. At this time, an average of more than 1,000 superabsorbent resin particles were targeted, and the pore sizes of more than 800 particles in which the pores were clearly visible were measured. Here, the standard for "clearly visible pores" is that, assuming that air bubbles are formed in a spherical shape, they are judged to be most clearly visible when they take on an almost hemispherical shape on the surface of the superabsorbent resin particles after the crushing process.
[0159] 4) Next, the final measured particle pore sizes of more than 800 particles were obtained, and the diameters of each were measured. Among these, the ratio of micropores with pore diameters of 2 μm to 180 μm was calculated and shown in Table 1.
[0160] 5) In addition, the average diameter was statistically calculated as the median value for the measured particle diameters, and the results are shown in Table 1. At this time, the quartile range was used to confirm the pore size distribution, in order to eliminate measurement errors due to the measuring probe and outliers.
[0161] FIG. 5(a) is a schematic cross-sectional image of the superabsorbent resin produced by the multi-stage foaming process of Example 1, and shows that a plurality of micropores exist inside the superabsorbent resin particles finally produced through polymerization, drying, pulverization, etc., and therefore the water absorption speed can be significantly improved. FIG. 5(b) is a schematic cross-sectional image of the superabsorbent resin produced by the single foaming process of Comparative Example 1, and shows that the average diameter of the pores is relatively large inside the superabsorbent resin particles finally produced through polymerization, drying, pulverization, etc., and therefore the improvement effect of the water absorption speed can be reduced compared to the Examples. FIG. 5(c) is a schematic cross-sectional image of the superabsorbent resin produced by the single foaming process of Comparative Example 4, and shows that the average diameter of the pores is the largest and the number of pores is the smallest inside the superabsorbent resin particles finally produced through polymerization, drying, pulverization, etc., and therefore the improvement effect of the water absorption speed can be reduced compared to the Examples.
[0162] Figure 6(a) shows a cross-sectional SEM image of the superabsorbent resin prepared by the multi-stage foaming process of Example 1, Figure 6(b) shows a cross-sectional SEM image of the superabsorbent resin prepared by the single foaming process of Comparative Example 1, and Figure 6(c) shows a cross-sectional SEM image of the superabsorbent resin prepared by the single foaming process of Comparative Example 4. Referring to Figure 6, it can be seen that in the examples, a large number of micropores are formed in the superabsorbent resin, which can significantly improve the water absorption rate.
[0163] Experimental Example 3: Measurement of the physical properties of superabsorbent resin The properties of the superabsorbent resins produced in the above Examples and Comparative Examples were evaluated by the following methods and are shown in Table 1 below.
[0164] Unless otherwise indicated, all of the following physical property evaluations were performed at room temperature (24±1° C.), and saline or salt water refers to a 0.9 wt % sodium chloride (NaCl) aqueous solution.
[0165] (1)Centrifuge Retention Capacity (CRC) The water retention capacity of each resin was measured by the water absorption capacity under no load using EDANA WSP 241.3.
[0166] Specifically, the highly water-absorbent resin W0(g) (approximately 0.2g) was evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was evacuated for 3 minutes at 250G using a centrifuge, and the mass of the envelope W2(g) was measured. The same procedure was also performed without using the resin, and the mass W1(g) at that time was measured. The CRC(g / g) was calculated using the obtained masses according to the following formula.
[0167] [Formula 1] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0168] (2) Water absorption rate (Vortex time) The water absorption rate (vortex time) of the superabsorbent resins of the above Examples and Comparative Examples was measured by the following method.
[0169] (i) First, 50 mL of 0.9% salt water was poured into a 100 mL beaker with a flat bottom using a 100 mL mass cylinder. (ii) Next, the beaker was placed so as to be located at the center of a magnetic stirrer, and then a circular magnetic bar (diameter 30 mm) was placed in the beaker. (iii) Thereafter, the stirrer was operated so that the magnetic bar was stirring at 600 rpm, and the lowest point of the vortex created by stirring was in contact with the magnetic bar. (iv) After confirming that the temperature of the salt water in the beaker had reached 24.0°C, 2±0.01 g of the superabsorbent resin sample was added and a stopwatch was started. The time until the liquid surface became completely horizontal while the vortex disappeared was measured in seconds, and this was regarded as the water absorption rate.
[0170] [Table 1]
[0171] Referring to the contents of Table 1, it was confirmed that the examples form a hierarchical pore distribution in the superabsorbent resin produced by carrying out a multi-stage foaming process using a bubble stabilizer, thereby exhibiting improved water absorption properties and water absorption speed.
[0172] In the case of Comparative Examples 1 to 3, which use a bubble stabilizer but do not undergo a multi-stage foaming process, it was difficult to form a hierarchical pore distribution, and as a result, it was confirmed that the water absorption rate was increased compared to the Examples.
[0173] In the case of Comparative Example 4, in which a multi-stage foaming process was performed but no foam stabilizer was used, it was difficult to form fine bubbles, and as a result, it was confirmed that the water absorption rate was significantly increased compared to the examples.
[0174] In addition, in the case of Comparative Example 5 in which a multi-stage foaming process was performed but a physical foaming process was also performed, it was confirmed that it was difficult to form fine bubbles, and as a result, the water absorption rate was significantly increased compared to the Examples.
Claims
1. preparing a monomer composition including a water-soluble acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, a polymerization initiator, and a first crosslinking agent; a step of subjecting the mixture obtained by mixing the monomer composition with a first foaming agent and a foam stabilizer to a primary foaming process; a step of subjecting the mixture obtained by the first foaming to a second foaming agent; a step of cross-linking and polymerizing the secondary foaming mixture to form a hydrogel polymer; drying, grinding and classifying the hydrogel polymer to form a base resin powder; and The method includes a step of crosslinking at least a portion of the surface of the base resin powder in the presence of a surface crosslinking agent. A method for producing a superabsorbent resin.
2. In the first foaming step, the concentration of the foam stabilizer relative to the total weight of the mixture is greater than the concentration of the foam stabilizer relative to the total weight of the mixture in the second foaming step. A method for producing the highly water-absorbent resin according to claim 1.
3. In the first foaming step, the foam stabilizer is included in an amount of 0.02 to 1.0 wt % based on the total weight of the mixture, In the second foaming step, the concentration of the foam stabilizer is smaller than that in the first foaming step. A method for producing the highly water-absorbent resin according to claim 1.
4. The foam stabilizer is a hydrophilic surface-modified compound; A method for producing the highly water-absorbent resin according to claim 1.
5. The foam stabilizer is a compound whose hydrophobic surface has been modified with one or more polymers selected from the group consisting of polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidine, polyvinyl acetate, polyvinylpyrrolidine, polyacrylic acid, polyacrylic amide, polydopamine, poly(4-styrenesulfonate), polyethylene glycol, and polypropylene glycol, or a copolymer thereof; A method for producing the highly water-absorbent resin according to claim 1.
6. The first and second blowing agents are each independently foamed at 50° C. or less. A method for producing the highly water-absorbent resin according to claim 1.
7. The first and second blowing agents are each independently one or more selected from the group consisting of sodium carbonate, sodium bicarbonate, potassium bicarbonate, azodicarbonamide, p,p'-oxybisbenzenesulfonylhydrazide, dinitrosopentamethylenetetramine, p-toluenesulfonylhydrazide, and benzenesulfonylhydrazide; A method for producing the highly water-absorbent resin according to claim 1.
8. In the secondary foaming step, further mixing a monomer composition including a water-soluble acrylic acid monomer having an acidic group, at least a part of which has been neutralized, a polymerization initiator, and a first crosslinking agent; A method for producing the highly water-absorbent resin according to claim 1.
9. The first and second foaming steps are each independently performed at 35°C to 50°C. A method for producing the highly water-absorbent resin according to claim 1.
10. In the first foaming step, fine bubbles having a diameter of 100 nm or less are formed, In the secondary foaming step, bubbles having a diameter of 100 nm to 300 nm are formed. A method for producing the highly water-absorbent resin according to claim 1.
11. The cross-linking polymerization step is carried out at 50°C to 100°C. A method for producing the highly water-absorbent resin according to claim 1.
12. The superabsorbent polymer contains a plurality of pores, the average diameter of the plurality of pores is 20 μm to 150 μm; Among the plurality of pores, 70% or more of the micropores have a diameter of 2 μm to 180 μm. A method for producing the highly water-absorbent resin according to claim 1.
Citation Information
Patent Citations
Highly water-absorbent resin and method for producing the same
JP2021505716A
Highly water-absorbent resin and method for producing the same
JP2021506989A
Highly water-absorbent resin and method for producing the same
JP2021517603A
Superabsorbent Polymer And Preparation Method Thereof
US20190248963A1